Friction and wear response of vegetable oils and their blends with mineral engine oil in a reciprocating sliding contact at severe contact conditions. (March 2018) - Bahari, Adli; Lewis, Roger; Slatter, Tom
Although many studies investigating the tribological performance of pure vegetable oils have been conducted, a better understanding of vegetable oil tribological performance at extreme conditions is still needed. Similarly, little work has been carried out to study the influence of the vegetable oils on the performance of a lubricant formed from a blend of vegetable oil and conventional mineral engine oil. This work presents the tribological performance of vegetable oils, and their blends with mineral oil, in a high temperature and contact pressure reciprocating contact. Palm- and soybean-based vegetable oils were mixed with a commercial mineral engine oil at a 1:1 ratio by volume. The conventional mineral oil was also tested to provide a benchmark. The pure palm oil exhibited lower friction than soybean oil, but for the wear performance, this was reversed. The friction performance of the palm oil was competitive to that of the mineral engine oil. The mineral engine oil was far superior in wear resistance over both vegetable oils. When blended with mineral engine oil, both vegetable oils demonstrated a reduction in coefficient of friction when compared to their pure oil states. An improvement in the wear performance was observed for both a blend of palm oil and mineral engine oil (25% improvement) and that of soybean and mineral engine oil (27% improvement). This work shows that for palm oil and soybean oil, the performance of a blended oil is influenced by its vegetable oil component and that tribological characteristics of vegetable oils are dominant. That said, the significant limitation of these vegetable oils is their ability to provide a satisfactory level of wear resistance. It is suggested that any future work in this area should have a greater emphasis on the enhancement of wear resistance.